Recent Clinical Characteristics of Labors Using Three Japanese Systems of Midwife-Led Primary Delivery Care - Shunji Suzuki (Hindawi Limited, 2016)
Objective. The objective of this study was to describe the recent clinical characteristics of labor using 3 systems of Japanese midwife-led primary delivery care, as follows: (1) those intending to give birth at home managed by midwives who do not belong to our hospital, (2) those planning to give birth in our hospital managed by the same midwives, and (3) those planning to give birth managed by midwives who belong to our hospital. Methods. A retrospective cohort study was performed. Results. There were no significant differences in the obstetric or neonatal outcomes among the 3 groups. The rate of transfers during labor with the system involving midwives belonging to our hospital was higher than those with the other 2 systems. In addition, the timing of transfers in the system with the midwives belonging to our hospital was earlier than with the other 2 systems. Among the 3 groups, there were no significant differences in the rate of the main 2 indications for transfers: fetal heart rate abnormality and failure to progress. Conclusion. There were no significant differences in perinatal outcomes among the 3 systems; however, there were some differences in the status of transfers to obstetric shared care.